CHEMICAL COMPOSITION OF ESSENTIAL OIL OF APIS MELLIFERA PROPOLIS FROM FALCON STATE, VENEZUELA - Rios, Nurby; Yanez, Carlos; Rojas, Luis; Mora, Flor; Usubillaga, Alfredo; Vit, Patricia (Emirates Journal of Food and Agriculture, 2014)
Apis mellifera bees obtain propolis by adding wax and salivary secretions to resinous, gummy or balsamic materials collected from various plant sources. Its chemical composition depends on many factors (type of bee, flora accessed, environment, management, season, vegetation and geographical area of collection). In the hive, the bees use propolis to consolidate structural components, varnish inside the cells and prevent vibrations. Propolis is known for its antibacterial, fungicidal, antiviral, anesthetic, antiulcer, immunostimulating, hypotensive, cytostatic, and antioxidant properties, the essential oil of Apis mellifera propolis, collected in Falcon state, was obtained by hydrodistillation using a Clevenger trap (0.06% yield). The oil was analyzed by gas chromatography coupled to mass spectrometry (GC / MS) in an HP GC-MS System Model 5973. Twentythree compounds were identified (93.6%), of which the three major compounds were germacrene D (26.5%), ?-caryophyllene (10.2%) and ?-elemene (8.1%).